2019
DOI: 10.21053/ceo.2019.00423
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Intraoperative Neuromonitoring System Using an Accelerometer Sensor in Thyroid Surgery: A Porcine Model Study

Abstract: Objectives. The sensitivity and positive predictive value of widely used intraoperative neuromonitoring (IONM) using electromyography (EMG) of the vocalis muscle in thyroid surgery are controversial. Thus, we developed a novel IONM system with an accelerometer sensor that uses the piezoelectric effect instead of EMG to detect laryngeal twitching. The objective of this study was to evaluate the feasibility and safety of this novel IONM system during thyroid surgery in a porcine model. Methods.We developed an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A previous study has reported that the pressure sensor has the same stimulus threshold as EMG in rabbits [27]. An accelerometer sensor placed in anterior neck skin and the posterior cricoid also has the same stimulus threshold as EMG in pigs [36]. These reports have suggested that the accuracy of the pressure sensor to identify laryngeal muscle twitching to assess RLN status is likely to be very similar to that of EMG.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study has reported that the pressure sensor has the same stimulus threshold as EMG in rabbits [27]. An accelerometer sensor placed in anterior neck skin and the posterior cricoid also has the same stimulus threshold as EMG in pigs [36]. These reports have suggested that the accuracy of the pressure sensor to identify laryngeal muscle twitching to assess RLN status is likely to be very similar to that of EMG.…”
Section: Discussionmentioning
confidence: 93%
“…A piezoelectric pressure sensor was modified to measure changes in skin surface pressure and to identify facial muscle movement [ 12 , 22 ]. The objective of the present study was to determine the feasibility and reliability of FNM using a surface pressure sensor in a rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…If either electrode has poor contact, accurate EMG measurements cannot be made. Therefore, instead of evaluating muscle movements using EMG, novel IONM systems that mea- [11,12]. In the future, these sensors can be further developed into skin adhesive sensors or endotracheal tube-attached sensors.…”
mentioning
confidence: 99%
“…If either electrode has poor contact, accurate EMG measurements cannot be made. Therefore, instead of evaluating muscle movements using EMG, novel IONM systems that measure muscle movements with a new single sensor, such as a surface pressure sensor or an accelerometer based on a piezo-electric sensor, have been introduced [ 11 , 12 ]. In the future, these sensors can be further developed into skin adhesive sensors or endotracheal tube-attached sensors.…”
mentioning
confidence: 99%